Calculus : early transcendentals - Anton, Howard; Bivens, Irl; Davis, Stephen (Singapore : John Wiley & Sons, 2013)
Anton, Bivens & Davis latest issue of Calculus Early Transcendentals Single Variable continues to build upon previous editions to fulfill the needs of a changing market by providing flexible solutions to teaching and learning needs of all kinds
1. Before calculus -- 2. Limits and continuity -- 3. The derivative -- 4. Topics in differentiation -- 5. The derivative in graphing and applications -- 6. Integration -- 7. Applications of the definite integral in geometry, science, and engineering -- 8. Principles of integral evaluation -- 9. Mathematical modeling with differential equations -- 10. Infinite series -- 11. Parametric and polar curves; conic sections -- 12. Three-dimensional space; vectors -- 13. Vector-valued functions -- 14. Partial derivatives -- 15. Multiple integrals -- 16. Topics in vector calculus
Includes index
International students version
Keywords: Calculus; Calculus -- Textbooks